Safety and Efficacy of the ACE-Inhibitor Ramipril in Alport Syndrome: The Double-Blind, Randomized, Placebo-Controlled, Multicenter Phase III EARLY PRO-TECT Alport Trial in Pediatric Patients. (1st July 2012) - Gross, Oliver; Friede, Tim; Hilgers, Reinhard; Görlitz, Anke; Gavénis, Karsten; Ahmed, Raees; Dürr, Ulrike
Abstract : Introduction . Retrospective observational data show that ACE-inhibitor therapy delays renal failure and improves life expectancy in Alport patients with proteinuria. The EARLY PRO-TECT Alport trial assesses the safety and efficacy of early therapy onset with ramipril in pediatric Alport patients. Methods and analysis . This double-blind, randomized, placebo-controlled, multicenter phase III trial (NCT01485978; EudraCT-number 2010-024300-10) includes 120 pediatric patients aged 24 months to 18 years with early stages of Alport syndrome (isolated hematuria or microalbuminuria). From March 2012, up to 80 patients will be randomized 1:1 to ramipril or placebo. In the event of disease progression during 3-year treatment, patients are unblinded and ramipril is initiated, if applicable. Approximately 40 patients receive open-label ramipril contributing to the safety database. Primary end-points are "time to progression to next disease level" and "incidence of adverse drug events before disease progression." Treatment effect estimates from the randomized comparison and Alport registry data will be combined in supportive analyses to maximize evidence. Conclusion . Without this trial, ACE inhibitors may become standard off-label treatment in Alport syndrome without satisfactory evidence base. The results are expected to be of relevance for therapy of all pediatric patients with kidney disease, and the trial protocol might serve as a model for other rare pediatric glomerulopathies.